Effect of Different Energy Drinks on Liver and Heart Enzymes in Rats - Backer, Wadiah S; Baeissa, Hanadi M (The International Journal of Biotechnology, 2014)
Eighteen-year-old Irish athlete was died as a result of playing a basketball game after consuming four cans of red bull in 2000. France, Denmark and Norway have banned red bull. Britain issued a warning against red bull use by pregnant women and children in 2001. There was very limited evidence that the consumption of energy drinks have any effect on the enzymes of our body. Therefore, the present study investigated the effects of six different types of energy drinks (Red Bull, Power Horse, Bison, Bugzy, Boom Boom, and Code Red) on liver and heart enzymes. One hundred forty seven male Wister rats were divided into seven groups in each group 21 rats. The first group is as control drinking water. The other six groups received orally the drink (1.8 ml/250 g/day)daily by gavage for 30 days. After 10, 20, and 30 days, the blood samples were collected from all groups to determined liver and heart enzymes. Inliver, the results showed a significant decrease of alanine aminotransferase concentration by drinking Bison, Bugzy, Boom Boom and Code Red groups. All energy drinking groups showed a significant decrease in the concentration of aspartate aminotransferase except in Red Bull group. Also, they showed decrease of alkaline phosphatase concentration except in Bison group. In heart, the results showed that creatine kinase concentration decreased significantly by all energy drinking groups except Red Bull and Bugzy. All energy drinking groups showed a significant decrease in the creatine kinase-MB concentration except in Bugzy group. As conclusions, most energy drinks may cause a disorder in liver and heart which effect the production of their enzymes.